Mathematics at High Courses in Kaunas: studies and teachers - Banionis, Juozas (Lietuvos matematikos rinkinys, 2010)
Notwithstanding unfavorable international context for Lithuania, which was caused by battles for Lithuania’s independence, and difficulties of public life related to that context, in 1920–1922 High Courses in Kaunas lay the foundation for Lithuanian University, which was established on February 16, 1922. The staff of High Courses, i.e. lecturers of mathematics (Z. Žemaitis, J. Graurogkas, etc.) formed the mathematical kernel of Lithuanian University to be opened. The first participants of High Courses became students of mathematic studies. The first teaching aids and books were purchased and accommodation for studies was found. It was the base for the university. Thus, High Courses performed the role of a predecessor of Lithuanian University. The departments formed at High Courses marked the beginning of the founding of the University and its Faculty of Mathematics and Natural Sciences.